Interactions of hydrophobic and hydrophilic self-assembled monolayers with water as probed by sum-frequency-generation spectroscopy - Howell, Caitlin; Maul, Robert; Wenzel, Wolfgang; Kölsch, Patrick (Chemical physics letters, 2010)
Hydrophilic and hydrophobic self-assembled monolayers of alkanethiols were examined in air and in water using sum-frequency-generation spectroscopy (SFG). Hydrophilic films showed significant changes in peak intensity and position upon exposure to water, indicating extensive interaction of water molecules with the film. Spectra of hydrophobic films were similar in air and water, indicating only weak interactions of water with the film. Density Functional Theory (DFT) calculations were also performed to identify the vibrational modes contributing most significantly to the observed effects. These results demonstrate how SFG can be used to detect the interaction of water with molecules in thin films at interfaces.